Local Case Studies - Abidi, Sohail; Mir, Aized H.; Durrani, Amer Z. (World Bank, Washington, DC, 2014)
The local case studies for projects in different sectors were prepared to document the bottlenecks which occurred during the various processes involved in the life cycle of infrastructure projects. Identifying such processes allows a better understanding of the capacity constraints in planning, designing, programming, procurement, contract administration, financing and budgeting, execution, and other stages in a project cycle. The case studies clearly demonstrate the presence of deep rooted systematic problems related to: (1) inadequate client capacity to plan, procure, program, administer, and manage projects; (2) imbalanced conditions of contracts; (3) flawed procurement procedures (pre-qualification, bid evaluation, negotiations, and re-negotiations with the lowest bidder) causing significant delays; (4) mismatched project funding needs and actual availability of funds; (5) commencement of projects without ensuring that required funds are in place; (6) delay in making running payments; (7) insufficient time given for detailed design and variations in contract due to inadequacies in design; (8) limited capacity of local contractors; and (9) poor international bid response in mega projects related to credibility issues.